2008
DOI: 10.1016/j.janxdis.2007.01.003
|View full text |Cite
|
Sign up to set email alerts
|

Recognition of facial expressions in obsessive–compulsive disorder

Abstract: Sprengelmeyer et al. [Sprengelmeyer, R., Young, A. W., Pundt, I., Sprengelmeyer, A., Calder, A. J., Berrios, G., et al. (1997). Disgust implicated in obsessive-compulsive disorder. Proceedings of the Royal Society of London, 264, 1767-1773] found that patients with OCD showed severely impaired recognition of facial expressions of disgust. This result has potential to provide a unique window into the psychopathology of OCD, but several published attempts to replicate this finding have failed. The current study … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
40
0

Year Published

2009
2009
2017
2017

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 47 publications
(42 citation statements)
references
References 72 publications
2
40
0
Order By: Relevance
“…Several studies have reported that when compared with healthy controls and patients with panic disorder and GAD, patients with OCD exhibit impaired recognition of dis gust, but normal recognition of other facial expressions, in cluding fear, 42,43 which has been confirmed in a recent meta analysis. 44 These results are counterintuitive, as one might expect that individuals with OCD would be very good at rec ognizing facial expressions of disgust, especially since they seem to experience disgust more readily than those without the disorder.…”
Section: J Psychiatry Neurosci 2017;42(5)mentioning
confidence: 72%
“…Several studies have reported that when compared with healthy controls and patients with panic disorder and GAD, patients with OCD exhibit impaired recognition of dis gust, but normal recognition of other facial expressions, in cluding fear, 42,43 which has been confirmed in a recent meta analysis. 44 These results are counterintuitive, as one might expect that individuals with OCD would be very good at rec ognizing facial expressions of disgust, especially since they seem to experience disgust more readily than those without the disorder.…”
Section: J Psychiatry Neurosci 2017;42(5)mentioning
confidence: 72%
“…About two-thirds of the sample was found to evidence this bias, and bias was not restricted to people with a more severe presentation of OCD or the prima facie speculation of greater involvement with contamination concerns. Corcoran et al 37 also did not observe an association between disgust recognition impairment and obsessive-compulsive symptom subtypes or other clinical factors that could account for within-group variability.…”
Section: Discussionmentioning
confidence: 90%
“…The administration of the POFA test was in accordance with the standardized procedure as outlined by Sprengelmeyer et al 30 whereby the stimuli were presented statically without alteration. This differs from the procedures used by other investigators (for example, Corcoran et al 37 and Parker et al 35 ), which used morphed facial stimuli expressions. Participants were presented pictures in random order on a Dell Inspiron 1100 laptop computer, with a 12-inch screen.…”
Section: Measures Procedure and Statisticsmentioning
confidence: 94%
See 2 more Smart Citations